Ethanol extract of Artemisia sieversiana exhibits anticancer effects and induces apoptosis through a mitochondrial pathway involving DNA damage in COLO-205 colon carcinoma cells - Jun Tang; Juan-Juan Zhao; Zhi-Hong Li (Bangladesh Pharmacological Society, 2015)
The aim of the study was to see the antiproliferative and apoptotic effects of ethanolic herbal extract of Artemisia sieversiana against three human colon cancer (HT-29, HCT-15 and COLO-205) cells. The cytotoxicity of the extract on these cell lines was evaluated by MTT assay. Phase contrast and fluorescence microscopy using acridine orange/ethidium bromide (AO/ETBR) staining was employed to investigate morphological alterations in COLO-205 cells by the herbal extract. Flow cytometry instrument measured the changes in mitochondrial membrane potential loss while as gel electrophoresis measured DNA damage in these cells. The extract at increasing doses exhibited a strong cytotoxic effect in a dose-dependent manner against all the three colon cancer cell lines. The IC50 values of the extract against HT-29, HCT-15 and COLO-205 cancer cells were found to be 52.1, 43.2 and 38.6 µg/mL respectively. Mitochondrial membrane potential loss (??m) and DNA fragmentation events were also observed following extract treatment at increasing doses.